2010
DOI: 10.1016/j.biocel.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proliferation and migration of vascular smooth muscle cells in response to vascular injury under hyperglycemic conditions is controlled by β3 integrin signaling

Abstract: Atheroma formation and restenosis following percutaneous vascular intervention involve the growth and migration of vascular smooth muscle cells (SMCs) into neointimal lesions, in part due to changes in the extracellular matrix. While some clinical studies have suggested that, in comparison to nondiabetics, β3 integrin inhibition in diabetic patients confers protection from restenosis, little is known regarding the role of β3 integrin inhibition on SMC responses in this context. To understand the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
1
33
0
1
Order By: Relevance
“…As previously reported [7,10,11,25] , both the PKC inhibitor Ro 31-8220 and the MEK1/2 inhibitor PD 98059 abrogated the high glucoseenhanced proliferation and migration of VSMCs. Thus, the PKC and MAPK pathways were both responsible for mediating the proliferative-and migratory-promoting response of VSMCs in high glucose medium.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As previously reported [7,10,11,25] , both the PKC inhibitor Ro 31-8220 and the MEK1/2 inhibitor PD 98059 abrogated the high glucoseenhanced proliferation and migration of VSMCs. Thus, the PKC and MAPK pathways were both responsible for mediating the proliferative-and migratory-promoting response of VSMCs in high glucose medium.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have demonstrated that VSMCs that are cultured under hyperglycemic conditions displayed enhanced proliferative and migratory responses compared to cells that are www.chinaphar.com He M et al Acta Pharmacologica Sinica npg cultured under euglycemic conditions, and it has been suggested that protein kinase C (PKC) signal transduction may play an important role in this effect [7,9,10] . Other studies have shown that activation of the mitogen-activated protein kinase (MAPK) pathway may contribute to the increased proliferation and migration of VSMCs in response to hyper glycemia [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Our data show that avb3 inhibitors potently inhibit smooth muscle incorporation into early spontaneous atherosclerotic plaques, phenocopying the early reduction in plaque smooth muscle content observed after the deletion of plasma fibronectin. 10 In contrast to avb3, expression of a5b1 is largely limited to plaque endothelial cells and macrophages, and inhibiting a5b1 limits early atherogenesis but does not prevent smooth muscle incorporation into early atherosclerotic plaques.…”
Section: Flow-induced Inflammation Requires Avb3mentioning
confidence: 67%
“…In vitro, diabetes appears to enhance vascular smooth muscle cell proliferation and migration through alterations in proteases, integrins, glycoproteins and formation of Advanced Glycation Endproducts (AGEs) (20,21). In vivo, elevated blood glucose levels have been shown to induce a series of alterations within the vasculature including endothelial dysfunction, cellular proliferation, changes in extracellular matrix conformation and impairment of LDL receptor-mediated uptake decreasing the in vivo clearance of LDL concentrations (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%